Critical Assessment on Unmet Oral Health Needs and Oral Health-related Quality of Life Among Old Age Home Inhabitants in Karnataka, India - M, Roma (Clin Cosmet Investig Dent, 2021)
PURPOSE: To critically assess the unmet oral health needs and oral health-related quality of life among old age home inhabitants in Karnataka, India. METHODS: A total of 96 older adults (males=32, 33.33%, females=64, 66.67%) aged 60 years and above, residing in old age homes were included in this cross-sectional study. The mean age of the participants included in the study was 69.25±7.99 years. Oral health status and dental needs were assessed using the Oral Hygiene Index Simplified (OHIS) and the WHO Oral Health Assessment forms. Oral health-related quality of life was evaluated by administrating the Geriatric Oral Health Assessment Index (GOHAI) questionnaire through an interview format. STATISTICAL ANALYSIS: The Statistical Package for Social Sciences (SPSS) version 17 was used. Descriptive statistics was tabulated for oral health status and GOHAI scores. Student’s t-test and ANOVA were applied to check the association of the GOHAI responses with the number of years of residence in old age homes, age groups, gender, and dentition status. RESULTS: The mean age of the participants included in the study was 69.25±7.99 years. Twenty-six (27.1%) participants reported diabetes mellitus and hypertension. Most of the participants 89 (91.7%) visited the dentist when they had dental complaints. Among the dentulous study population, the majority of the participants had untreated dental caries indicated for dental extraction and needed periodontal therapy. Amongst the participants, 68 (70.82%) required prosthetic rehabilitation. More than 10 years of residence in old aged homes, over 80 years of age, being female, and completely edentulous groups showed lower total GOHAI scores compared to their counterparts. CONCLUSION: The majority of the participants showed unmet oral health needs and lower GOHAI scores indicating poor oral health-related quality of life.